Vaccination of chickens with a temperature-sensitive mutant of Salmonella enteritidis - Cerquetti, Maria Cristina (2000)
One-day old chickens were inoculated with temperature-sensitive mutant E/1/3 of S. enteritidis. Two routes of inoculation were used: oral and intraperitoneal (ip). One group of chickens were given two oral inoculations (oral-oral). A second group received two ip inoculations (ip-ip). A third group received the first dose orally and the second ip (oral-ip) and the fourth group was given the first dose ip and the second dose orally (ip- oral). The vaccine strain was safe even when inoculated at high doses, and induced strong protection against virulent S. enteritidis strain after oral challenge. Results show that vaccination with mutant E/1/3 reduced the number of animals shedding the pathogen after challenge. Furthermore, animals immunized oral-oral and oral-ip showed a significant reduction in cecal and spleen colonization by virulent Salmonella.